KAJIAN FILM DALAM PERSPEKTIF SASTRA MODERN - Mukodas; Miranti (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study aims to explain the place of film within the framework of modern literature, specifically as an object of literary study and a narrative-audiovisual cultural text. Literature is often limited to written verbal works, even though modern literary theory has expanded its scope to include texts, narratives, signs, representations, ideologies, and layers of meaning. This study employs a Systematic Literature Review method following the PRISMA 2020 guidelines. Data were obtained through a search of articles on Crossref and Google Scholar using the Publish or Perish tool. From an initial 1,061 records, 120 final articles were selected that met the inclusion criteria: scientific journal articles, published between 2020 and 2026, with film as the primary object of study, employing literary theory or perspectives, and available in full text. The data were analyzed through narrative synthesis by mapping the year of publication, theoretical approaches, aspects of study, and the position of film within modern literary studies. The results of the study indicate that film studies from a literary perspective are dominated by screen adaptation or media adaptation, accounting for 45 articles (37.5%), followed by literary sociology with 29 articles (24.2%), literary psychology with 19 articles (15.8%), feminism and gender with 11 articles (9.2%), narratology with 6 articles (5.0%), semiotics with 4 articles (3.3%), and general approaches with 6 articles (5.0%). These findings demonstrate that films are not merely studied as adaptations of literary works but also as independent texts that possess their own narrative structures, systems of signs, conflicts, representations, ideologies, and layers of meaning. This study affirms that film is more appropriately situated as an object of modern literary study and as a narrative-audiovisual cultural text, since the expansion of literary studies lies in the expansion of ways of reading, not in blurring the boundaries between written literature and film.